Use of dried basil in the technology of Hamburgers buns - Hubenia, Vyacheslav; Ishchenko, Tatiana (My University, 2023)
The expediency of using spicy-aromatic raw materials in the technology of hamburger buns, namely dried basil, is substantiated. The results of research on the influence of raw materials on the technological process of the production of hamburger buns are presented. With the help of laboratory studies, the effectiveness of using this raw material in the production of bakery products has been proven.

Обґрунтовано доцільність використання пряноароматичної сировини в технології булочок для гамбургерів, а саме базиліку сушеного. Представлено результати досліджень впливу сировини на технологічний процес виробництва булочок для гамбургерів. За допомогою лабораторних досліджень доведено ефективність використання даної сировини у виробництві хлібобулочних виробів.
Keywords: кафедра готельно-ресторанної справи; bread; porosity; acidity; moisture; restaurant; hamburgers buns; basil; хліб; пористість; кислотність; вологість; ресторан; булочки для гамбургерів; базилік